Redefining cultural identity in digital art practice: Artistic journeys across cultural boundaries and ethnic borders - Song, Borim (My University, 2009)
During the past several decades, globalization has blurred the borders among cultures, to some extent. The development of computers and the Internet has accelerated the collapse of cultural boundaries and changed the way people experience cultures; thus, defining one’s cultural identity is now a more complicated process. These changes imply that approaching the concept of cultural identity in the new artistic practice of digital art cannot be based only on a traditional understanding of what culture means in society and how it interacts with art.
Keywords: Cultural Identity; Digital Art; Art Education